Inovasi Psikologis : Membangun Resiliensi dan Kreativitas Wirausaha di Era Digital - Fitriani Fitriani; Arfian Arfian (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Entrepreneurs in the digital era face constant challenges that require adaptation and innovation. Although economic and managerial factors are often the focus, the role of psychological dimensions such as resilience and creativity in entrepreneurial success has not been widely reviewed in depth. This study aims to examine relevant theories and findings on psychological resilience and creativity in the context of entrepreneurship, and to build a conceptual framework to support entrepreneurial innovation. Using a qualitative literature study method, this study systematically searches, analyzes, and synthesizes scientific literature from various databases. The results of the synthesis indicate that psychological resilience is crucial for entrepreneurs to recover from failure and adapt to change. Characteristics such as optimism and emotional regulation are the pillars of mental resilience. Meanwhile, creativity is an innovation engine that facilitates the identification of new opportunities and the development of unique solutions. A synergistic relationship between resilience and creativity is also found: resilience provides a psychological buffer for taking creative risks, and the creative process can strengthen self-resilience. The theoretical implication is the need for a more holistic entrepreneurship model. In practice, this study recommends educational institutions, especially the Faculty of Psychology, to integrate the development of resilience and creativity into the entrepreneurship curriculum.